EFEKTIFITAS LATIHAN FISIK DAN YOGA DENGAN KECEMASAN LANSIA DI SAMARINDA - Bachtiar Safrudin Lubis (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2022)
Background: The aging process is a natural process accompanied by a decrease in physical, psychological and social conditions that interact with each other. Anxiety disorders are one of the decline in psychological conditions, anxiety disorders. The increase in stressors was exacerbated by the Covid-19 pandemic. One of the interventions that can affect anxiety is physical exercise and yoga. Objective: This study aims to determine the effect of yoga practice on anxiety levels in the elderly. Research Methods: This study uses a quasi-experimental approach with a pre-post group design without control approach. The number of samples with purposive sampling as many as 22 people. The data obtained were tested with the Wilcoxon Test. Research Results: The test results obtained a value of p = 0.000 p < (0.05), meaning that H0 is rejected, which means that there is an effect of physical exercise and yoga on anxiety in the elderly during the Covid-19 pandemic at the Tresna Werdha Nirwana Puri Samasinda Home. Conclusion: There is an effect of yoga practice on decreasing anxiety scores in the elderly.